Land use and groundwater quality in the upper Agno watershed (Loo and Cayapas Valleys, Northern Benguet) - Pascua, Chelo Supnet (2000)
Loo Valley is a relatively small watershed (<50 km²) dominated by agricultural land use that its impacts on the local water resources are severe and pronounced. The adjacent Cayapas Valley is similar in drainage size, geology, climate, topography and meteorology with significant contrast in land use. By comparing these two small watersheds, the effects of the land use on the local groundwater quality in Loo Valley can be assessed. Nitrate (NO₃) concentration in shallow domestic wells dug in alluvium (>6 meters depth) in Loo Valley show a three-fold increase due to seasonal change. The range of values of the three shallow domestic wells located in the floodplain post 10-47 mg/L during the dry season to 24 to 146 mg/L during the wet season. Five monitoring wells (1 to 2 meters depth) installed within the floodplain and distributed at similar distances from each towards the downstream direction, show relatively similar nitrate levels during the dry season (10 to 24 mg/L). However, nitrate levels in the monitoring wells experienced a cumulative increase towards the downstream direction ranging from 24 mg/L to 73 mg/L during the wet season. Such trend in nitrate levels consequently implies increased likelihood of the downstream areas to contamination and possible pollution. Nitrate (NO₃) levels in perennial springs of the Loo Valley did not vary appreciably during the change in season. Dry season nitrate levels range from 13 to 22 mg/l to 14 to 23 mg/l during the wet season. Average nitrate concentration in groundwater of forested areas in Cayapas Valley ranges less than 6 mg/L and did not vary appreciably in perennial springs during the dry and wet seasons. Using the >6 mg/L as the nitrate background level to compare nitrate levels , the shallow groundwater resources in Loo Valley are contaminated with nitrates (NO₃). Springs used as potable water resources in the Loo Valley are contaminated but are less than the prescribed maximum contaminated levels (MCL) of <40 mg/L (NO₃). Shallow domestic wells in the Loo Valley temporarily exceed the MCL for nitrates due to seasonal change, which indicates leaching of the excess nitrates in the soil. Intermittent springs (found only during the wet season) in Loo and Cayapas valleys have very high nitrate concentrations. In Loo Valley, the observed nitrate levels from these intermittent springs range from 25 to 54 mg/L while in Cayapas Valley, nitrate levels range from 18 to 44 mg/L. These intermittent springs with high nitrate levels pose a threat to the water quality of the potable water resources from nearby perennial springs. Factors leading to the observed nitrate concentrations in groundwater of Loo and Cayapas valleys include (1) modification of the natural drainage system, (2) farming practices regarding fertilizer use and alteration of the topography, (3) land use distribution, (4) continuity of the hydrogeologic regimes, (5) trend of geologic structures and the (6) geomorphology of the Loo Valley. The slight variation in nitrate levels of the Cayapas Valley can be attributed to mixing with contaminated groundwater and could indicate possible interbasin interaction through geologic structures resulting to groundwater contamination. Agricultural contributions pose a six-fold increase in the suspended sdeiment yield of the Loo Valley compared to Cayapas Valley. Silt + clay-sized particles in the suspended sediment yield increases with an increase in contributing agricultural land use. This is shown by the opposing trends in the suspended sediment yield analyzed towards the downstream direction in both valleys. the source of the fine-grained fraction in the Loo valley is attributed to soil erosion in the sloping vegetable farms and road construction. On the other hand, landslides are the major contributors in the Cayapas Valley.
"December 2000."
Research project funded by UNiversity through the Office of the Vice-Chancellor for Research and Development (OVCRD).-- (UARD-12196T, UARD-12197T)
Thesis (M.S. Geology)--University of the Philippines Diliman.
Keywords: Groundwater -- Quality. -- Philippines -- Loo Valley (Benguet); Groundwater -- Quality. -- Philippines -- Cayapas Valley (Benguet); Water -- Nitrogen content -- Philippines -- Loo Valley (Benguet); Water -- Nitrogen content -- Philippines -- Cayapas Valley (Benguet); Land use -- Philippines -- Loo Valley (Benguet); Land use -- Philippines -- Cayapas Valley (Benguet)